Acute myeloma kidney and SARS-COV2 infection with dialysis need: never say never - a case report - Gabriele Donati; Agnieszka Przygocka; Fulvia Zappulo; Gisella Vischini; Sabrina Valente; Gaetano La Manna (BMC Nephrology, 2023)
Abstract Background Older individuals with multiple comorbidities and especially patients with multiple myeloma are at higher risk of contracting SARS-CoV-2. When patients with multiple myeloma (MM) are also affected by SARS-CoV-2 the time to start immunosuppressants is still a clinical dilemma especially when urgent hemodialysis is required for acute kidney injury (AKI). Case presentation We present a case of an 80-year-old woman who was diagnosed with AKI in MM. The patient began hemodiafiltration (HDF) with free light chain removal combined with bortezomib and dexamethasone. The reduction of free light chains concurrently was obtained by means of HDF using poly ester polymer alloy (PEPA) high-flux filter: 2 PEPA filters were used in series during each 4-h length HDF session. A total of 11 sessions was carried out. The hospitalization was complicated with acute respiratory failure caused by SARS-CoV-2 pneumonia successfully treated with both pharmacotherapy and respiratory support. Once the respiratory status stabilized MM treatment was resumed. The patient was discharged in stable condition after 3 months of hospitalization. The follow up showed significant improvement of the residual renal function which allowed interruption of hemodialysis (HD). Conclusions The complexity of patients affected by MM, AKI, and SARS-CoV-2 should not discourage the attending physicians to offer the adequate treatment. The cooperation of different specialists can lead to a positive outcome in those complicated cases.